Advanced biology - Kent, Michael (Oxford : Oxford University Press, 2000)
Providing complete coverage of the new A- and AS-level core specifications, this textbook presents concepts in separate double-page spreads. Each spread starts with learning objectives and ends with questions to test understanding
Keywords: Problems and exercises biology; Biologie Problèmes et exercices